Different response of the oxygen pathway in patients with chronic thromboembolic pulmonary hypertension treated with pulmonary endarterectomy versus balloon pulmonary angioplasty - Fu, Zhihui; Tao, Xincao; Xie, Wanmu; Yang, Peiran; Gao, Qian; Wang, Jinzhi; Zhai, Zhenguo (Frontiers in Cardiovascular Medicine, 2022)
Background Oxygen pathway limitation exists in chronic thromboembolic pulmonary hypertension (CTEPH). Pulmonary endarterectomy (PEA) and balloon pulmonary angioplasty (BPA) are two effective interventions for CTEPH, but their effects and comparison of these two interventions on the oxygen pathway are not well demonstrated. Methods CTEPH patients with available pulmonary function test, hemodynamics, and blood gas analysis before and after the interventions were included for comparison of oxygen pathway in terms of lung ventilation, lung gas exchange, oxygen delivery, and oxygen extraction between these two interventions. Results The change in the percentage of the predicted forced expiratory volume in the 1 s (−3.4 ± 12.7 vs. 3.8 ± 8.7%, P = 0.006) and forced vital capacity (−5.5 ± 13.0 vs. 4.2 ± 9.9%, P = 0.001) among the PEA group (n = 24) and BPA group (n = 46) were significantly different. Patients in the PEA group had a significant increase in their arterial oxygen saturation (from 92.5 ± 3.6 to 94.6 ± 2.4%, P = 0.022), while those in the BPA group had no change, which could be explained by a significant improvement in ventilation/perfusion (−0.48 ± 0.53 vs. −0.17 ± 0.41, P = 0.016). Compared with patients post-BPA, patients post-PEA were characterized by higher oxygen delivery (756.3 ± 229.1 vs. 628.8 ± 188.5 ml/min, P = 0.016) and higher oxygen extraction (203.3 ± 64.8 vs. 151.2 ± 31.9 ml/min, P = 0.001). Conclusion Partial amelioration of the oxygen pathway limitations could be achieved in CTEPH patients treated with PEA and BPA. CTEPH patients post-PEA had better performance in lung gas exchange, oxygen delivery, and extraction, while those post-BPA had better lung ventilation. Cardiopulmonary rehabilitation may assist in improving the impairment of the oxygen pathway.